Designing Instagram Feeds to Promote Tabungan Emas Using Figma Application at Pegadaian Jombang - Dyah Putri Anggraini; Heru Utomo (INDO PUBLISHING, 2025)
Social media promotion on Instagram aims to provide product-related information from companies with a broad reach. Observations have shown that offline promotion methods are less effective for the target, and social media has not been optimally utilized for promotion. This research aims to design an Instagram feed that can be used as a promotional medium on Pegadaian Jombang's Instagram social media.This research used an action research method with research stages of planning, action, observation, and reflection. Data collection was carried out through interviews, observations, documentation, and questionnaires. The respondents in this study consisted of 21 individuals, including 2 marketing experts, 2 design experts, 2 Pegadaian Jombang marketing staff, and 15 customers.The research was conducted through 2 cycles. In cycle 1, the effectiveness score was 3.8, and in cycle II, the effectiveness score increased by 0.8 to 4.6. This indicated that the Instagram feed design was categorized as very effective.From this research, it can be concluded that the Instagram feed design created is suitable for publication and is very effective for use as a promotional medium. Therefore, it is recommended that companies remain consistent in creating subsequent content and further enhance their creativity in this digital marketing era.